Studi Kinerja Ekonomi dan Nilai Tambah Agroindustri Tempe di Kota Mataram - Wuryantoro Wuryantoro; Taslim Sjah; I Ketut Budastra; Sri Supartiningsih; Sri Maryati; Candra Ayu (Universitas Mataram, 2022)
Tempe is an agro-industrial product that uses soybean as raw material. Within the framework of agricultural development, agro-industry is the main driver of the development of the agricultural sector. Agro-industry is expected to be able to produce high added value and be managed efficiently. The aim of this research is to analyze the level of economic performance and to find out the amount of added value created from the tempe agroindustry activities. The study used a descriptive method, while the data was collected using a survey technique by interviewing 15 tempe entrepreneurs as respondents. To answer the objectives of this study, the collected data were analyzed using economic feasibility analysis and Hayami. The results showed that the tempe agroindustry in Mataram City produced good economic performance and was feasible to be cultivated with the resulting R/C ratio of 2.2 and a rate of return on capital of 121%. The added value obtained from processing one kilogram of soybeans into tempeh is Rp. 5 769 with a value added ratio of 34.34%.